The stone girl : a novel - Wittenborn, Dirk (W.W. Norton & Company, 2020)
"The Lost Boys had numbers and firepower, but Evie Quimby knew the wilderness. For several generations, an elite circle of rich and powerful men has, by malfeasance, murder, and marriage, built a secret and impregnable empire. They call themselves The Lost Boys, and within the stately confines of an Adirondack fortress, lay the plans that carry them around the globe, infiltrating lives and fortunes. Their violations are casual and devastating - especially of those who unwittingly fit their purposes. Set in the Adirondacks and Paris, The Stone Girl is a novel of psychological suspense in which three women- each scarred by a chain of misfortune, theft, and death-by the hands of The Lost Boys, seeks a reckoning. Eve Quimby was raised wild in the Adirondacks. At 17, her life changes when she meets Lulu Mannheim, an heiress haunted by family legacies. Their friendship raises Evie to unlikely heights as an art restorer in Paris. It also makes her the target of the most predatory Lost Boy. When Chloe, Evie's daughter is diagnosed with leukemia and an elegant stranger brings her flowers, the women are pulled back into a snare they thought they'd escaped"--